Doctor-patient confidentiality - right and duty of a doctor in law regulations - Jaroszyński, Janusz; Husarz, Renata; Jurek, Anna; Mela, Aneta (Journal of Education, Health and Sport, 2018)
Physician’s professional secrecy is one of the most important duties of a doctor and should be provided with confidentiality regarding his or her health. Generally speaking, there is no legal definition of "physician’s professional secrecy" in Poland, although this concept already appears in the oath of Hippocrates: ‘I will keep secret anything I see or hear professionally which ought not to be told’. The issue of medical confidentiality (physician’s professional secrecy) has been regulated in several legal acts such as: The Patient Rights and Patients Ombudsman Act, The Constitution of the Republic of Poland, The Medical Profession Act, The Civil Code Act, The Criminal Code Act and Code of Medical Ethics which is not considered as a legal act. The patient has the right to require confidentiality of the information concerning him and the obligation to keep medical confidentiality will apply to every representative of the medical profession, who obtained certain information by various professional activities.